Bauran Pemasaran Mako Cake And Bakery Di Mega Mall Manado - Losung, Vega Savra; Kaunang, Rine; Montolalu, Maya Hendrietta (Sam Ratulangi University, 2024)
This study aims to describe the marketing mix at Mako Cake and Bakery Mega Mall Manado outlet. This research was carried out at Maco Cake And Bakery in Mega Mall Manado, and the research time is 2 (two) months, the data used in this research is primary and secondary data, the sampling method uses the Qualitative Descriptive Method. Based on the results of interviews conducted, this research shows that the location/distribution channel strategy in this marketing mix is very profitable for the Mako Cake and Bakery Outlet in Mega Mall Manado, the reason is because it is located near the entrance which is easy to find, and also the ease of transportation to reach the location which is in the city center. The marketing mix results for product, price, place and promotion have been carried out well. In terms of products, it is in accordance with the motto of Mako cake and bakery, namely High-quality, refined, and delicious bread and pastries or high- quality, smooth and delicious bread and pastries.